2013
DOI: 10.1021/ie3024214
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surfactants in Mechanical Degradation of Drag-Reducing Polymers

Abstract: Turbulent drag reduction behavior of mixed polymer–surfactant systems (anionic polymer/cationic surfactant; nonionic polymer/cationic surfactant; nonionic polymer/anionic surfactant) was studied in a pipeline flow loop to explore the role of surfactants in mechanical degradation of polymers. The polymers investigated were nonionic polyethylene oxide (PEO) and anionic polyacrylamide (PAM). The surfactants studied were cationic octadecyltrimethylammonium chloride (OTAC) and anionic sodium dodecyl sulfate (SDS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…The effect of drag reduction of flow by high molecular polymer or surfactants has also some limitations which come from the properties of additives. The main disadvantage of high molecular polymers is their susceptibility to mechanical and thermal degradation (Kim et al, 2000;White and Mungal, 2008;Mohsenipour and Pal, 2013a). In case of surfactant solutions, it is a certain critical Reynolds number exceeding of which results in the loss of micelles orientation and the collapse of the DR effect (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of drag reduction of flow by high molecular polymer or surfactants has also some limitations which come from the properties of additives. The main disadvantage of high molecular polymers is their susceptibility to mechanical and thermal degradation (Kim et al, 2000;White and Mungal, 2008;Mohsenipour and Pal, 2013a). In case of surfactant solutions, it is a certain critical Reynolds number exceeding of which results in the loss of micelles orientation and the collapse of the DR effect (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In case of surfactant solutions, it is a certain critical Reynolds number exceeding of which results in the loss of micelles orientation and the collapse of the DR effect (Wang et al, 2011). The addition of surfactant to polymer solution effectively reduces polymer degradation process, especially when the flow temperature of the solution is high (Kim et al, 2000;Mohsenipour and Pal, 2013a). The phenomenon of the fluid flow drag reduction by simultaneous addition of the high molecular polymer and the surfactant with salt additives into the solvent is still a relatively new and poorly recognized issue.…”
Section: Introductionmentioning
confidence: 99%
“…The present investigations have shown that polymers or surfactants alone as the drag‐reducing agent have certain advantages and disadvantages due to their properties. For instance, polymers can induce the efficient drag reduction at a relatively low concentration, but they are susceptible to thermal or/and mechanical degradation at the intense shear or the high temperature . Such degradation is permanent and irreversible, which leads to lost in the drag reduction function.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the injection of a certain surfactant into drag‐reducing solution of polymers alleviates the degradation of polymer molecular chains effectively. This is because surfactant micelles and polymer molecular chains interact to form new conformations helpful to improve the drag reduction efficacy . Accordingly, it is vital for obtaining a high and stable drag reduction rate to investigate the synergistic influence of polymers and surfactants on the drag reduction deeply.…”
Section: Introductionmentioning
confidence: 99%
“…WLM behave like linear polymer chains and can entangle into a tri-dimensional network, therefore imparting huge viscoelasticity to the solutions. Due to the desirable viscoelasticity, WLMs systems have found extensive applications as rheology control reagents in home and personal care, drag reduction [2], oil exploration, hydraulic fracturing, drug release [3], etc.…”
Section: Introductionmentioning
confidence: 99%